The effect of capital intensity, earnings management and independent commissioners on tax avoidance - Nila Senny; Suparna Wijaya (WIM Solusi Prima, 2026)
This study examines the effect of capital intensity, earnings management, and independent commissioners on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using a quantitative approach with secondary data from financial and annual reports, this study applies purposive sampling and obtains 59 companies with 180 firm-year observations. Tax avoidance is measured using three proxies, namely ETR, CETR, and BTD, to capture different perspectives. Data were analyzed using multiple linear regression with STATA 12. The results show that capital intensity positively affects tax avoidance when measured by ETR and CETR, but negatively affects tax avoidance when measured by BTD. Earnings management does not affect tax avoidance under the ETR model, but has a negative effect under the CETR and BTD models. Meanwhile, independent commissioners have no significant effect on tax avoidance across all three models.